Renegotiation and the Impossibility of Optimal Investment - Persons, John C. (Review of Financial Studies, 1994)
In a model with asymmetric information and external equity financing, it is impossible to achieve socially optimal investment because of renegotiation possibilities. The contractual solution suggested by Dybvig and Zender (1991) is not dynamically consistent–the manager's contract would be renegotiated, resulting in inefficient investment. Moreover, no other compensation contract that would induce the manager to invest efficiently survives renegotiation. Contracts that pay the manager based on the stock price, while producing suboptimal investment as in Myers and Majluf (1984), are robust to renegotiation. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.